2009
DOI: 10.1074/jbc.m109.004465
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Critical Residues of the MyD88 Death Domain Involved in the Recruitment of Downstream Kinases

Abstract: MyD88 couples the activation of the Toll-like receptors and interleukin-1 receptor superfamily with intracellular signaling pathways. Upon ligand binding, activated receptors recruit MyD88 via its Toll-interleukin-1 receptor domain. MyD88 then allows the recruitment of the interleukin-1 receptor-associated kinases (IRAKs). We performed a site-directed mutagenesis of MyD88 residues, conserved in death domains of the homologous FADD and Pelle proteins, and analyzed the effect of the mutations on MyD88 signaling.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
56
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 40 publications
(48 reference statements)
6
56
0
Order By: Relevance
“…These features of the protein can be analyzed by dualtag coimmunoprecipitation assays (homodimerization and recruitment of IRAKs) and by reporter gene assays (NF-B activation). 18 By following this strategy, we were able to identify 3 residues that are required for the interaction of MyD88 with IRAKs and for MyD88-dependent activation of NF-B. 18 Remarkably, mutations in one of these residues, glutamic acid 52, was also found in patients affected by recurrent infections, 19 which thus validated our in vitro studies in a physiopathologic setting.…”
Section: Myd88 Inhibition and Human Diseasessupporting
confidence: 55%
See 2 more Smart Citations
“…These features of the protein can be analyzed by dualtag coimmunoprecipitation assays (homodimerization and recruitment of IRAKs) and by reporter gene assays (NF-B activation). 18 By following this strategy, we were able to identify 3 residues that are required for the interaction of MyD88 with IRAKs and for MyD88-dependent activation of NF-B. 18 Remarkably, mutations in one of these residues, glutamic acid 52, was also found in patients affected by recurrent infections, 19 which thus validated our in vitro studies in a physiopathologic setting.…”
Section: Myd88 Inhibition and Human Diseasessupporting
confidence: 55%
“…18 By following this strategy, we were able to identify 3 residues that are required for the interaction of MyD88 with IRAKs and for MyD88-dependent activation of NF-B. 18 Remarkably, mutations in one of these residues, glutamic acid 52, was also found in patients affected by recurrent infections, 19 which thus validated our in vitro studies in a physiopathologic setting. Our studies also revealed that the small stretch of residues in the DD of MyD88, constituted by the ␣1, ␣2, ␣3 helices and by the first portion of the ␣4 helix, offers a surface of interaction between MyD88 and IRAKs.…”
Section: Myd88 Inhibition and Human Diseasessupporting
confidence: 55%
See 1 more Smart Citation
“…Myc-tagged MyD88 TIR, Myc-tagged MyD88, Myc-tagged IRAK1-kinase-dead (KD) (K239S), and Myc-tagged IRAK4-KD (KK213AA), were constructed as described previously (13,27,28). All constructs for the expression of mutated MyD88 TIR or MyD88 were generated by PCR using oligonucleotides containing the mutated residues.…”
Section: Plasmids-expression Vectors For Flag-tagged Myd88 Ormentioning
confidence: 99%
“…MyD88 has a modular structure with a death domain (DD) at the N terminus, an intermediate linker domain (ID), and a TIR domain at the C terminus (10). The DD presents a fold that resembles a Greek key bundle of six antiparallel ␣-helices (11) and allows MyD88 oligomerization and its interaction with the respective DDs of the serine-threonine kinases IRAK1/2/4, thus resulting in a multimeric complex named Myddosome (12,13). This complex propagates the signal and leads to activation of transcription factors, such as the nuclear factor B (NF-B), * This work was supported by grants from Fondazione Italiana Sclerosi Mul-the activator protein 1, and the interferon-regulatory factors, and of mitogen-activated protein kinases (MAPKs), such as the stress kinase p38 and the extracellular signal-regulated kinases 1 and 2 (ERK1/2) (14).…”
mentioning
confidence: 99%